The Impact of New Technologies on Economic Growth – A Panel Data Analysis - Anna GALIK; Maciej CZAPLEWSKI (Communications of International Proceedings, 2021)
The paper explores the impact of new technologies on economic growth. A panel data analysis was conducted for 32 countries (Austria, Belgium, Bulgaria, Croatia, Cyprus, Czech Republic, Denmark, Estonia, Finland, France, Germany, Greece, Hungary, Iceland, Ireland, Italy, Latvia, Lithuania, Malta, Netherlands, Norway, Poland, Portugal, Romania, Serbia, Slovakia, Slovenia, Spain, Sweden, Switzerland, Turkey the United Kingdom). The research covers a period of 10 years from 2009 to 2018 and is based on Eurostat data. The analysis aims to establish the impact of new technologies on the rate of economic growth. It verifies whether empirical data supports the concept that the more significant the role of the high technology sector then this results in more substantial economic growth and thus an increase in the wealth of society.
Keywords: Economic Growth; Economic Development; Gross Domestic Product (GDP); New Technology